Islamic Dilemma Studies in College Islamic Religion: Analysis of IAIN Purwokerto Student Academic Passion for Islamic Studies Subjects - Umar, Muhammad Toha (International Conference of Moslem Society, 2019)
Islamic studies (Islamic studies) in several Islamic Religious Colleges (PTKI) seem to find new challenges in the form of "UIN" ization that open several majors / general study programs within the scope of PTKI. In addition, the transfer of titles from what originally attributed "religion", "Islam", or "Sharia" behind the scholarship degree (S.Ag, S.Pd.I, SHI) becomes without penance (S.Pd. SH), as well as the competence of graduates who increasingly push the competence of ulema, making Islamic studies must really appear competitive so that students are interested. This paper will try to see how students at IAIN Purwokerto have dialectics with the variety of scholarships offered, especially Islamic scholarship which must look for interested people in the midst of a number of vocational courses and professions that are not included in Islamic studies.